Controller for stand alone room lighting powered by wind energy: article / Mat Nizam Mahmud - Mahmud, Mat Nizam
The primary focus in this project is to design the suitable charge controller for prototype of stand-alone room lighting powered by wind energy. This controller design will provide the protection to the battery during the charging and discharging activities. This is due to battery charger have it limiter for upper and lower voltage.